Designing training and instructional programs for older adults - Czaja, Sara J.; Sharit, Joseph (New York : CRC Press, 2013)
"Current and emerging trends in the domains of health management and the work sector, the abundance of new consumer products pervading the marketplace, and the desires of many older adults to undertake new learning experiences means that older adults, like their younger counterparts, will need to continually engage in new learning and training. Thus, understanding the challenges that older people face when confronted with new learning and training programs and developing potential strategies to overcome them is imperative. A comprehensive state-of-the-science review, Designing Training and Instructional Programs for Older Adults explores a broad range of issues, from the implications of theories of learning for designing instruction for older adults to adapting current perspectives on methods of instructional design to accommodate the capabilities and limitations of older learners. The authors provide an understanding of today's older adults, their demographics, their needs, the challenges facing them, and a realistic appraisal of their abilities and limitations's a basis for how current knowledge about training and instructional design should be shaped and applied to best accommodate this population of learners. They discuss topics such as retention and transfer of training, sequencing the order of instruction, e-learning, multimedia training formats, and the assessment and evaluation of training programs from the perspective of issues relevant to older learners. They also highlight the challenges presented by this very heterogeneous group that varies tremendously in backgrounds, skills, knowledge, and abilities.Focusing on how learning occurs, the authors' balanced coverage makes the book readable and enlightening across a wide spectrum of professionals and academics, including human factors/ergonomics specialists, gerontologists, managers, educators, undergraduate and graduate students, and the design community. The book supplies concise recommendations that will have direct impact on the design of instructional programs and for those individuals who are responsible for the training and performance of older people"--
"Preface Our goal in writing this book was to draw on an understanding of today's older adults--including their demographics, their needs, the challenges facing them, and a realistic appraisal of their abilities and limitations--as a basis for how current knowledge about training and instructional design should be shaped and applied to best accommodate this population of learners. With rapidly emerging technologies, including those in the domains of health management and the work sector, as well as the many products that are continually pervading the consumer market that are capable of positively affecting the quality of life of many older adults, understanding the barriers that older people may face in learning to use these resources is imperative. The literature on training and instructional design is not only extensive but has a relatively long history. Many of the developments in these areas were driven by the desire to improve learning in our educational institutions and the training of our military and industrial personnel. One of the key challenges in writing this book was to distill knowledge from these vast areas that would be relevant to the problem of training and instructional design for older adults. This was necessary in part because there is no theory of training and instruction that is directed solely toward this population of learners. There are stretches throughout this book where it may seem that the older learner has been neglected as we examine in some depth topics fundamental to or related to training and instruction. However, we have tried as much as possible to ensure that these discussions always relate back to the primary subject of this book, the older learner"--
"A CRC title, part of the Taylor & Francis imprint, a member of the Taylor & Francis Group, the academic division of T&F Informa plc."
Includes bibliographical references and index.
Keywords: Older people -- Education; Instructional systems -- Design; Aging -- Psychological aspects; BUSINESS & ECONOMICS / Human Resources & Personnel Management; TECHNOLOGY & ENGINEERING / Industrial Health & Safety